Advanced oxidation processes for the removal of natural organic matter: Design and construction of a treatment rig - Taylor, C.; Visser, D.; Joll, Cynthia; Heitz, Anna; Von Gunten, Urs (International Water Association IWA, 2009)
A treatment rig incorporating several advanced oxidation process (AOP) methods (utilising ozone, peroxide, UV, ferrate (Fe(VI)), and photo-Fenton's reagent) has been designed and is being constructed at a laboratory scale suitable for simulating plant conditions. The rig will be used to study the removal of natural organic matter (NOM) from waters by various AOP methods, in various combinations, with the overall goal of removal by DBP, particularly emerging DBP precursors.